Shale Gas Development and Drinking Water Quality - Hill, Elaine; Ma, Lala (American Economic Review, 2017)
Recent studies have linked shale gas development (SGD) to ground water contamination. The extent of these environmental externalities, to date, remains uncertain. To address this gap, we examine whether shale gas development systematically affects drinking water quality by creating a novel dataset that relates SGD to public drinking water samples in Pennsylvania. Our difference-in-differences strategy finds evidence that additional well pads drilled within 1 kilometer of a community water system intake increases shale gas-related contaminants in drinking water. These results are striking considering that our data are based on water sampling measurements taken after municipal treatment.